ANALISIS KINERJA UPT BALAI LATIHAN KERJA DALAM MENINGKATKAN KUALIATAS SDM DI KABUPATEN SUMBAWA - Kusuma, Aksal Anugra; Fitriyani, Ika; Sutama, I Nyoman (Jurnal Ekonomi & Bisnis, 2024)
This study aims to analyze the performance of UPT BLK of Sumbawa District in improving the quality of human resources in Sumbawa District. The type of this study was descriptive study with a quantitative approach. The type of data used in this study was quantitative data obtained from documents found at the UPT BLK of Sumbawa District. The data to be studied in this study was collected using documentation techniques. The use of documentation techniques in this study aims to collect financial data and the number of participants who took part in training at the UPT BLK of Sumbawa District in 2020-2022 from documents available at the UPT BLK of Sumbawa District. The analysis technique used to measure the performance of UPT BLK of Sumbawa District using the Balance Scorecard (BSC) concept which is based on four assessment perspectives, namely the financial perspective, consumer satisfaction perspective, internal business process perspective, and learning and growth perspective. The results of this study indicate that the performance of the Sumbawa Regency BLK UPT in 2020-2022 from a financial perspective and a customer perspective is in the fairly good category, while the performance of the Sumbawa Regency BLK UPT in 2020-2022 from an internal business process perspective and a growth and learning perspective is in the good category. This showed that UPT BLK of Sumbawa District had carried out its responsibilities well in implementing training programs for the community so that it is expected to improve the quality of human resources in Sumbawa District.